From weakness to recovery a case report on Kocher-Debre Semelaigne syndrome - Rai, Nishmith; Sharif, Mumtaz; Pal, Rajdeep; Hedaginal, Vinaykumar; Mehta, Rachna (International Journal of Contemporary Pediatrics, 2025)
Kocher-Debre-Semelaigne syndrome is a rare hypothyroid myopathy in children, characterized by muscle pseudohypertrophy and associated systemic symptoms. We report the case of a 5-year-old girl who presented with progressive muscle weakness, cold intolerance, dry skin, and constipation over seven months with prominent calf muscle hypertrophy, proximal muscle weakness, and hypotonia. This case underscores the importance of prompt diagnosis and treatment of KDSS to reverse symptoms and avoid misdiagnosis as a primary muscle disorder. Awareness is crucial for timely intervention and improved patient outcomes as hypothyroidism can be treated with thyroxine replacement therapy.